Performance profiles and training load of Optimist sailors - Walker, C. N. (University of Stellenbosch, 2020)
Introduction: Despite a growth in competitive sailing, there remains a lack of research available supporting performance analysis and athlete monitoring in sailing. To understand more about the Optimist sailing class, fundamental research into competitive sailing racing and training is needed. Therefore, the overarching aims of this dissertation were to i) determine race performance indicators of high-level Optimist sailing races and ii) to quantify the training loads within different wind intensities of competitive South African Optimist sailors. A secondary aim was to develop an Optimist race performance profile from the IODA Optimist World Championships. Methods: The dissertation was structured in three parts; part 1 involves a scoping review, which identifies the gaps within the current literature, part 2 establishes race performance indicators and uses these to develop performance profiles of high-level Optimist races, while part 3 is considers the training stress imposed on Optimist sailors during training sessions in different wind intensities. Part 2 followed a retrospective descriptive study design, 28 performance indicators were identified through statistical analyses and sailing coaches input. These were used to build a performance profile of 150 Optimist races from the IODA Optimist World Championships (2014-2018). Performance profiles were developed for the qualifying series and each fleet within the final series. Part 3 was an observational study which monitored 12 high-level competitive South African Optimist sailors during 21 on-water sailing training sessions in varying wind intensities (light, medium and strong). The training loads during the training sessions were monitored using heart rate measures, to determine TRIMP (Training Impulse) and the SHRZ (Summated-Heart-Rate-Zone) score, as well as the session-rating of perceived exertion method. A relationship between these measures and energy expenditure was also determined. Results: Results in part 2 showed almost perfect relationships between positions at each mark and the final race outcome for all series (rho=0.93-0.98, p<0.01). A regression analysis coupled with input from coaches determined time difference from race leader at all marks and the finish, as well as difference in velocity made good from race winner in leg 1 for qualifications and finals as the most important performance indicator predictors. The five variables were inversely associated with less or more time leading to a higher or lower rank for final race outcome. For part 3, session-RPE was higher in strong vs. light wind intensities (p=0.02). The TRIMP scores related to energy expenditure during all wind intensities (rho=0.35-0.82). The SHRZ method showed highest total training time in zone 2 (31%; aerobic system) and zone 3 (26%; anaerobic glycolysis system). Conclusion: Coaches can use the race performance indicators and performance profiles to compare race performances and subsequently give more specific feedback to the sailors. Wind intensity applies an external stimulus to the sailor, thereby contributing to internal load on the sailor. Therefore, using the TRIMP measure for internal load is recommended. This dissertation provides a greater understanding of the race performance indicators and training loads of high-level competitive Optimist sailors. The methods identified and utilised in these investigations may prove useful to sailing coaches when analysing their Optimist sailors` performance during competition and training.